Silent night, deadly night [videorecording (DVD)] - Nelson, Mike P. (Film director); Campbell, Rohan, 1997-; Modine, Ruby, 1990-; Brown, Dave (David Lawrence) (Actor); Tomlinson, David (Actor); Acheson, Mark (Cineverse Entertainment Corp., 2026)
When a drifter haunted by guilt becomes the vessel for an ancient, vengeful spirit, Christmas takes a deadly detour. For 24 nights leading up to Christmas, Billy is forced to don a Santa suit and punish those the spirit deems "naughty."